ANALISIS PERBANDINGAN SIFAT ALIRAN PADA MODEL 2D AXISYMMETRIC DENGAN MODEL 3D DENGAN METODE NUMERIK - Hendrarsakti, Jooned; Prakoso, A. D.; Montreano, Donny (Bina Teknika, 2016)
Many previous studies of ejector have been conducted to understand and maximize the ejector performance. The study can be in form of experiments, analytical, and numerical simulation. The numerical simulation looks for the most effective and efficient effort and time in modeling flow process inside the ejector. Model simplification becomes one of solution in conducting simulation effectively. Three dimensional models in general are applied to an ejector that would be analyzed. These models can be compared to the simpler model, namely axisymmetric 2D model. The current study investigated the comparison between 3D and 2D models using numerical solution. Three types of ejectors from different application were used as the objects of the study. The analysis was conducted by comparing the qualitative and quantitative results. The results show that qualitatively the 2D axisymmetric model has good comparison to the 3D model. Quantitatively, 2D axisymmetric model has good similarity to 3D model for ejector performance parameters, such as entrainment ratio and Mach number with biggest difference of 5.7%. However, the velocity and pressure distribution have bigger discrepancies at both axial and radial directions at the area with extreme change, such as at throat nozzle. It can be concluded that the 2D axisymmetric model can be used as substitution of 3D model when the objective is only to obtain ejector performance and qualitative study.